2022
DOI: 10.1093/plphys/kiac588
|View full text |Cite
|
Sign up to set email alerts
|

Agave REVEILLE1regulates the onset and release of seasonal dormancy inPopulus

Abstract: Deciduous woody plants like poplar (Populus spp.) have seasonal bud dormancy. It has been challenging to simultaneously delay the onset of bud dormancy in the fall and advance bud break in the spring, as bud dormancy and bud break were thought to be controlled by different genetic factors. Here, we demonstrate that heterologous expression of the REVEILLE1 gene (named AaRVE1) from Agave (Agave americana) not only delays the onset of bud dormancy but also accelerates bud break in poplar in field trials. AaRVE1 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…In plant breeding, various methods such as intervarietal selection, wide hybridization, transgene incorporation, and genome editing have been widely employed to enhance stress tolerance and other desirable traits [28][29][30][31][32]. Wild rice germplasms have been extensively demonstrated to be a source of stress resistance genes for rice breeding programs [17].…”
Section: Discussionmentioning
confidence: 99%
“…In plant breeding, various methods such as intervarietal selection, wide hybridization, transgene incorporation, and genome editing have been widely employed to enhance stress tolerance and other desirable traits [28][29][30][31][32]. Wild rice germplasms have been extensively demonstrated to be a source of stress resistance genes for rice breeding programs [17].…”
Section: Discussionmentioning
confidence: 99%
“…Studies on Japanese pear have shown that upregulation of PpEBB expression during the early stages of bud dormancy release acts on the promoters of cell cycle (CYCD) genes (Anh Tuan et al, 2016). Additionally, Liu et al, demonstrated that heterologous expression of agave AaRVE1 in poplar can both delay bud dormancy in autumn and accelerate bud sprouting in spring (Liu et al, 2022a). Tan et al, used linkage mapping to investigate the tea bud sprouting index by mapping quantitative trait loci (QTLs).…”
Section: Introductionmentioning
confidence: 99%